Petrografia, geoquímica e geocronologia dos Riolitos do noroeste do Ceará – Alvos: Penanduba, Mumbaba e Jordão - FEITOSA, Jeremias Vitório Pinto (2019)
The so-called rhyolite Penanduba (FRE-02), rhyolite Mumbaba (SOB-02) and rhyolite Jordão (SOB-05), targets of this study are located within the context of the Province Borborema (PB), state of Ceará. In general, these rocks have characteristics similar petrographically are porphyritic rocks with levels ranging from 68-75% SiO2, classified as porphyritic rhyolites, and in case of a rhyolite porphyry target Penanduba milonitizado because of its characteristics. The geochemical data allowed the classification of these rocks as rhyolites, metaluminous and belong to the shoshonitic series. Rare Earth Elements in the diagram shows an interlace pattern for the samples, showing a greater enrichment of LREE compared to HREE with a small anomaly Eu. The geochronology not possible to define the crystallization age of these rocks, however the data showed the precursor of some of these rocks may have a common genesis, due to the ages of 1.72 Ga., target Penanduba and 1.88 Ga. Target Mumbaba are nearby. As for the target Jordão, accused the zircons ages between 2.3 and 2.6 Ga. Before it is more plausible to consider the possibility that the zircons in this rock are "legacy", since the crystallization of that body must have occurred towards the end of the Neoproterozoic.